A study to assess the unmet need for contraception among married women in the rural field practice area of a medical college Jhansi - Arya, Vimal; Singh, Ashish K. (International Journal Of Community Medicine And Public Health, 2021)
Background: The concept of unmet need for family planning points to the gap between some women’s reproductive intentions and their contraceptive behaviour. Methods: A community based cross-sectional study was conducted from April 19 to March 20 in rural Jhansi. 520 married women (15-49 years) were interviewed by house to house survey. Results: Out of 520 participants 124 (23.8%) had unmet need, out of them 73 (14.03%) had unmet need for spacing births and 41 (9.8%) of the participants had unmet need for limiting births. Conclusions: The unmet need for contraceptives was 23.8% in the study which is much higher compared to NFHS-4 data for urban UP (19.6%), and it has to be taken in to consideration by policy makers.